2007
DOI: 10.2753/mtp1069-6679150105
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Credit Card Misuse Among College Students: The Mediating Role of Impulsiveness

Abstract: Credit card misuse has negative long-term consequences for marketers. The study investigates the role that personality plays in students' credit card misuse. Mowen's 3M hierarchical model of personality is applied to survey data from 254 college students; and four elemental personality traits-emotional instability, introversion, materialism, and the need for arousal-are found to be positively associated with credit card misuse. Impulsiveness emerges as a significant central trait that mediates these effects. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
120
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(142 citation statements)
references
References 37 publications
9
120
0
13
Order By: Relevance
“…However, impulse consumers tend to give in to their buying temptation although they are aware of the negative consequences (Rook, 1987). When the impulse is out of control, the impulsive consumers have a great tendency to misuse their credit cards because credit cards provide a readily accessible means to fulfil their self-generated desires for things (Pirog & Roberts, 2007;Rook & Fisher, 1995;Roberts & Jones, 2001). …”
Section: Impulsive Buyingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, impulse consumers tend to give in to their buying temptation although they are aware of the negative consequences (Rook, 1987). When the impulse is out of control, the impulsive consumers have a great tendency to misuse their credit cards because credit cards provide a readily accessible means to fulfil their self-generated desires for things (Pirog & Roberts, 2007;Rook & Fisher, 1995;Roberts & Jones, 2001). …”
Section: Impulsive Buyingmentioning
confidence: 99%
“…Consistent with Sirgy (1998), Dittmar, Long and Bond (2007) found that individuals who are materialistic are less satisfied and more likely to be compulsive buyers. Therefore, the desire to attain social status through material possessions can easily trigger temptation, causing splurge spending which probably lead to credit card misuse (Fitzmaurice, 2008;Pirog & Roberts, 2007;Richins, 2011). Rischins and Rudimin (1994) suggested that materialistic tendencies are related to the individual's identity, social behaviour, motivation for work and use of money.…”
Section: Materialismmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, unplanned behaviour can lead to negative outcomes such as unnecessary spending or post-purchase regret [36][37][38], the use of a BRS can directly influence unplanned booth visits and impulse purchasing behaviour, and a BRS may arouse hedonic desires and stimulate desires for fun and excitement related to unplanned booth visits [26]. These desires may be increased and nurtured by unplanned experiences, which produce revisit intentions at exhibitions in customers for whom an unplanned impulse purchase conveys a favourable evaluation of their behaviour [38][39][40].…”
Section: Continued Brs Use Unplanned Booth Visits and Revisit Intenmentioning
confidence: 99%
“…Issues involving credit or debt have been widely investigated by economic psychologists (Boddington & Kemp, 1999, Davies & Lea, 1995, Gardarsdóttir & Dittmar, 2012, Gathergood, 2012, Kim & Devaney, 2001, Lea, Webley & Levine, 1993, Lea, Webley & Walker, 1995, Livingstone & Lunt, 1992, Mewse, Lea & Wrapson, 2010, Norvilitis & MacLean, 2010, Norvilitis et al, 2006, Norvilitis, Szablicki & Wilson, 2003, Perry, 2008, Pirog III & Roberts, 2007, Roberts & Jones, 2001, Seaward & Kemp, 2000, Stone & Maury, 2006, Tokunaga, 1993, Vio, 2008, Wang, Lu & Malhotra, 2011, Webley & Nyhus, 2001 aiming to understand the psychological profile, especially from the behavioral standpoint, of individuals who are more likely to take loans, become indebted and have debt problems. Besides the demographic variables, these studies (ibid.)…”
Section: Introductionmentioning
confidence: 99%